2013
DOI: 10.1063/1.4803154
|View full text |Cite
|
Sign up to set email alerts
|

Temporal properties of secondary drop breakup in the bag-stamen breakup regime

Abstract: The situation of liquid drop bag-stamen breakup in a continuous air jet flow is investigated by a high speed camera. Test liquids include water, ethanol, and various glycerol mixtures. First, the morphology of bag-stamen breakup is observed and analyzed. The bag-stamen breakup range is found to be in good agreement with the model obtained by Rayleigh-Taylor instability. Then the disk and stamen deformation properties, the fragment average size, and size distribution of ring and stamen are researched in detail,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 35 publications
10
42
0
Order By: Relevance
“…At the stages near the sheet breakup (t>4.5ms), both schemes predict increasing deformation in the z-direction (with a slightly better behaviour for the BFW scheme) which contradicts the experimental data. On the other hand, similar trends in increasing deformation were observed in the experimental works of (Cao et al, 2007;Jain et al, 2015;Zhao et al, 2013), while the over-estimation of the crossstream diameter was also present in the detailed simulations of (Jain et al, 2015) for…”
Section: Sheet Thinning Breakup (We=32)supporting
confidence: 81%
See 2 more Smart Citations
“…At the stages near the sheet breakup (t>4.5ms), both schemes predict increasing deformation in the z-direction (with a slightly better behaviour for the BFW scheme) which contradicts the experimental data. On the other hand, similar trends in increasing deformation were observed in the experimental works of (Cao et al, 2007;Jain et al, 2015;Zhao et al, 2013), while the over-estimation of the crossstream diameter was also present in the detailed simulations of (Jain et al, 2015) for…”
Section: Sheet Thinning Breakup (We=32)supporting
confidence: 81%
“…care is usually taken in order to minimize the boundary layer of the free jet and obtain A C C E P T E D M A N U S C R I P T 5 a more uniform gas velocity; see selectively (Krzeczkowski, 1980), (Liu and Reitz, 1997), (Lee and Reitz, 2000), (Cao et al, 2007), (Opfer et al, 2012;Opfer et al, 2014), (Flock et al, 2012), (Zhao et al, 2010;Zhao et al, 2013), (Guildenbecher and Sojka, 2011), (Jain et al, 2015) among others. Details for these techniques can be found in (Guildenbecher et al, 2009) among others.…”
Section: ) Among Others)mentioning
confidence: 98%
See 1 more Smart Citation
“…The increased growth rate of D max for all the regimes is essentially owing to the higher pressure caused by the stagnation of the gas in the bag which results in a radial outward force on the rim [8]. The change in the growth rate of D for different We has been attributed to higher RT instability growth rates corresponding to higher values of drop acceleration, a, with increasing We [56]. Chou & Faeth [8] suggested the following empirical relation for the bag breakup regime, and Zhao et al [56] suggested the following for the bag-stamen breakup mode:…”
Section: (E) Disc Characteristics and Rim Formationmentioning
confidence: 99%
“…The change in the growth rate of D for different We has been attributed to higher RT instability growth rates corresponding to higher values of drop acceleration, a, with increasing We [56]. Chou & Faeth [8] suggested the following empirical relation for the bag breakup regime, and Zhao et al [56] suggested the following for the bag-stamen breakup mode:…”
Section: (E) Disc Characteristics and Rim Formationmentioning
confidence: 99%